Comics and Translation with a Multimodal Perspective in the Early Republican Era - Öztürk, Göksel; Tarakçıoğlu, Aslı Özlem (Border Crossing, 2020)
Comics has a “hybrid” interaction emerging from the “interplay” between pictorial and textual elements. However; many studies on comics translation focus on texts but disregarding pictures. Analyses performed by focusing on textual elements disregard pictorial and textual interactions, which is a kind of regression of the multimodal aspect of comics. One of the aims of this article is to treat comics on its own autonomy since comics is generally considered as a tool of other research areas. The present study investigates the functions of pictures and texts in the context of “pictorial turn” by keeping multimodal approach in perspective. Translated comics to be analysed are the first translated comic strips into Turkish after the alphabet reform. The very first concealed translations of comics during the Early Republican Era are analysed with a multimodal perspective considering historical context as well as cross-media interactions of pictures and texts. As the first Turkish translations of comics were published in children’s periodicals in the early Republican era, this article practices on multiple layers such as transformation of media, culture planning, and manipulation.